Application of whey protein hydrolysate as a technological additive in the sour cream production - Nikolina Anna; Neverova Olga; Rogozinnikova Irina; Pavlova Yana; Shamilov Rustam (BIO Web of Conferences, 2024)
In the context of economic sanctions, the problem of supplying food additives, including stabilizers and thickeners, which are important in the production of fermented milk products, remains relevant for many enterprises; the development of a fermented milk product – sour cream, using whey protein hydrolysate as a technological additive is relevant. The purpose of the research was to study the effect of whey protein hydrolysate on the technological process of manufacturing a fermented milk product, sour cream, and the quality indicators of the final product. The results of the acidity study showed that in the experimental samples, the ripening process occurred faster than in the control sample. Based on the results of the research, it can be concluded that whey protein hydrolysate can be used as a technological additive in the production of fermented milk products to improve quality indicators.